The Honeycomb Metaphor for Knowledge Integration: A Symbiotic Model for Human Resource Development in Islamic Higher Education - Fajri, Muhamad (JURNAL AL-TANZIM, 2026)
This study aims to analyze the concept of Human Resource (HR) development through the metaphorical philosophy of the hive, bees, and honey, and examine its relevance to the integration of knowledge, lecturer professionalism, and social contribution. This study uses a qualitative, case-study approach. Data collection techniques included interviews, observations, and documentation. Data analysis was conducted interactively, including content analysis and interpretive analysis of field findings. The results show that the university is understood as a “hive” that provides structure and governance, human resources as productive, collaborative, and benefit-oriented “bees,” and knowledge as the “honey” produced and disseminated to the community. Competency data collection and career planning for lecturers have been carried out, but the implementation of job acceleration, feedback mechanisms, and knowledge-based development is still limited. The philosophy of the hive, bees, and honey emphasizes the integration of spiritual, intellectual, and professional values, as well as the relevance of the curriculum and tridharma activities to community needs. The research provides implications that the philosophy of the hive, bees, and honey encourages integrated human resource development—spiritual, intellectual, and professional—strengthening lecturer collaboration, supporting career planning, increasing the relevance of the tridharma for society, and encouraging curriculum innovation and academic services.